The language of lying — Noah Zandan (TEDxChania, 2014)
: Μουσική Μουσική Συγγνώμη, το τηλέφωνο μου πέθανε. Δεν είναι τίποτα. Είμαι καλά. Αυτές οι εφαρμογές είναι ολοκληρωμένα. Η εταιρεία δεν ήταν γνωστή σε κανένα πρόβλημα. Μουσική Σου αρέσουν. Βλέπουμε πάνω από 10-200 πράγματα. Και πέθαμε πολλά από την ιστορία μας, για να βοηθήσουμε τις τρόπους να τα καταστρέψουν. Από τα μηδιωτικά εξοπλισμόρια, στους πολυγράφους, το πλήρωμα της πόλης, τους μονατέρες της πόλης, τους ανοιχτήρους, τους ανοιχτήρους, τους ανοιχτήρους, τους ανοιχτήρους, τους ανοιχτήρους, τους ανοιχτήρους, τους ανοιχτήρους, τους ανοιχτήρους, τους ανοιχτήρους, τους ανοιχτήρους, τους ανοιχτήρους, τους ανοιχτήρους, τους ανοιχτήρους, τους ανοιχτήρους. plutôt than the person we are. But while our brain is busy dreaming, it's letting plenty of signals slip by. Our conscious mind only controls about 5% of our cognitive function, including communication, while the other 95% occurs beyond our awareness. And according to the literature on reality monitoring, stories based on imagined experiences are qualitatively different from those based on real experiences. This suggests that creating a false story about a personal topic takes work and results in a different pattern of language use. A technology known as linguistic text analysis has helped to identify four such common patterns in the subconscious language of deception. First, liars reference themselves less when making deceptive statements. They write or talk more about others, often using the third person to distance and disassociate themselves from their lie. Which sounds more false? Absolutely no party took place at this house, or I didn't host a party here. Second, liars tend to be more negative, because on a subconscious level, they feel guilty about lying. For example, a liar might say something like, sorry, my stupid phone battery died. I hate that thing. Third, liars typically explain events in simple terms, since our brains struggle to build a complex lie. Judgment and evaluation are complex things for our brains to compute. As a U.S. president once famously insisted, I did not have sexual relations with that woman. And finally, even though liars keep descriptions simple, they tend to use longer and more convoluted sentence structure, inserting unnecessary words in irrelevant but factual sounding details in order to pad the lie. Another president confronted with a scandal proclaimed, I can say categorically that this investigation indicates that no one on the White House staff, no one in this administration presently employed was involved in this very bizarre incident. Let's apply linguistic analysis to some famous examples. Take seven time Tour de France winner Lance Armstrong. When comparing a 2005 interview in which he had denied taking performance enhancing drugs to a 2013 interview in which he admitted it, his use of personal pronouns increased by nearly three quarters. Note the contrast between the following two quotes. First, okay, you know, a guy in a French in a Parisian laboratory opens up your sample, you know, Jean Francis so and so, and he tests it. And then you get a phone call from a newspaper that says we found you to be positive six times for EPO. Second, I lost myself in all of that. I'm sure there would be other people that couldn't handle it, but I certainly couldn't handle it, and I was used to controlling everything in my life. I controlled every outcome in my life. In his denial, Armstrong described a hypothetical situation focused on someone else, removing himself from the situation entirely. In his admission, he owns his statements, delving into his personal emotions and motivations. But the use of personal pronouns is just one indicator of deception. Let's look at another example from former senator and US presidential candidate John Edwards. I only know that the apparent father has said publicly that he is the father of the baby. I also have not been engaged in any activity of any description that requested, agreed to, or supported payments of any kind to the woman or to the apparent father of the baby. Not only is that a pretty long-winded way to say the baby isn't mine, but Edwards never calls the other parties by name, instead saying that baby, the woman, and the apparent father. Now let's see what he had to say when later admitting paternity. I am Quinn's father. I will do everything in my power to provide her with the love and support she deserves. The statement is short and direct, calling the child by name and addressing his role in her life. So how can you apply these lie-spotting techniques to your life? First, remember that many of the lies we encounter on a daily basis are far less serious than these examples, and may even be harmless. But it's still worthwhile to be aware of telltale clues like minimal self-references, negative language, simple explanations, and convoluted phrasing. It just might help you avoid an overvalued stock, an ineffective product, or even a terrible relationship.